2013
DOI: 10.1371/journal.pone.0069119
|View full text |Cite
|
Sign up to set email alerts
|

Homo floresiensis Contextualized: A Geometric Morphometric Comparative Analysis of Fossil and Pathological Human Samples

Abstract: The origin of hominins found on the remote Indonesian island of Flores remains highly contentious. These specimens may represent a new hominin species, Homo floresiensis, descended from a local population of Homo erectus or from an earlier (pre-H. erectus) migration of a small-bodied and small-brained hominin out of Africa. Alternatively, some workers suggest that some or all of the specimens recovered from Liang Bua are pathological members of a small-bodied modern human population. Pathological conditions pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 64 publications
(116 reference statements)
2
11
0
2
Order By: Relevance
“…Initially it was suggested that H. floresiensis was a dwarfed H. erectus, but the burden of subsequent analyses suggests that it may be more closely related to a more primitive hominin such as H. habilis sensu stricto (Tocheri et al, 2007;Argue et al, 2009;Brown and Maeda, 2009;Morwood and Jungers, 2009). Other researchers have suggested that no new taxon needs to be erected because they claim the "Homo floresiensis hypodigm" has been sampled from a population of Homo sapiens-most likely related to the smallstatured Rampasasa people who live on Flores todayafflicted by either an endocrine disorder or a range of syndromes that include microcephaly, or who retain primitive morphology (see Baab et al, 2013 andWestaway et al, 2015 for refutations of these hypotheses).…”
Section: Ma To the Presentmentioning
confidence: 99%
“…Initially it was suggested that H. floresiensis was a dwarfed H. erectus, but the burden of subsequent analyses suggests that it may be more closely related to a more primitive hominin such as H. habilis sensu stricto (Tocheri et al, 2007;Argue et al, 2009;Brown and Maeda, 2009;Morwood and Jungers, 2009). Other researchers have suggested that no new taxon needs to be erected because they claim the "Homo floresiensis hypodigm" has been sampled from a population of Homo sapiens-most likely related to the smallstatured Rampasasa people who live on Flores todayafflicted by either an endocrine disorder or a range of syndromes that include microcephaly, or who retain primitive morphology (see Baab et al, 2013 andWestaway et al, 2015 for refutations of these hypotheses).…”
Section: Ma To the Presentmentioning
confidence: 99%
“…The skeletal remains of this new species are known from the Late Pleistocene strata at Liang Bua, a limestone cave on the island. Morphology of its cranium, endocast, mandible, shoulder girdle, pelvis, limb bones, hand, and foot have been described, analyzed, and interpreted (Brown et al, 2004;Morwood et al, 2005;Falk et al, 2005Falk et al, , 2009Argue et al, 2006Argue et al, , 2009Larson et al, 2007Larson et al, , 2009Tocheri et al, 2007;Gordon et al, 2008;Baab and McNulty, 2009;Brown and Maeda, 2009;Fransiscus, 2009, 2012;Jungers et al, 2009a, b;Lyras et al, 2009;Aiello, 2010;Kaifu et al, 2011;van Heteren, 2012;Baab et al, 2013;Jungers, 2013;Kubo et al, 2013;Orr et al, 2013;Daegling et al, 2014). However, not all the dental remains have been described in sufficient detail, and there even exists controversy as to whether the dental morphology of H. floresiensis is primitive or modern (Jacob et al, 2006;Brown and Maeda, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Those data led us to reexamine facial asymmetry data for LB1. Our nonstandard but repeatable measurements (3) were dictated by the statement (1) that, on the LB1 skull, most standard craniometric landmarks could not be recognized, as recently confirmed (22) but persistently ignored (25,42). The correspondence between our measurement patterns on LB1 facial bone landmarks and those for DS soft tissue points (41) is striking, given the comparison of absolute distances in our data with published frequencies (not magnitudes) of asymmetric linear distances (Table S1).…”
Section: Match Of Lb1 To Ds Patient Signsmentioning
confidence: 95%